Block polymer, cross-linked block copolymer comprising block copolymer, sulfur-carbon composite material, and method for manufacturing sulfur-carbon composite material
By using block copolymer and sulfur-carbon composite materials in lithium-sulfur batteries, lithium polysulfide leaking from the positive electrode is solved, and the capacity reduction and life shortening caused by the migration of lithium polysulfide in lithium-sulfur batteries is achieved. Maintain and extend lifespan.
Patent Information
- Application Number
- CN202380053036.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-18
AI Technical Summary
The lithium polysulfide leaking from the positive electrode in lithium-sulfur batteries migrates to the negative electrode, resulting in a reduced battery capacity and shortened life.
Using a block copolymer and a sulfur carbon composite material, the block copolymer consists of a first repeat unit with a pyrene group and a second repeat unit with a cationic functional group, and the crosslinked block copolymer is formed by crosslinking and coated. Distributed on the porous carbon material, combining sulfur compounds to form a sulfur-carbon composite material to capture lithium polysulfide.
Effectively prevent lithium polysulfide from leaking from the positive electrode, reduce its migration to the negative electrode, maintain the charging and discharge capacity of lithium sulfur batteries, and improve battery life.
Smart Images

Figure CN119487091A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a block copolymer capable of capturing polysulfide leaked from a positive electrode to improve battery life and a secondary battery comprising the same.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0110368 filed in Korea on August 31, 2022, the disclosure of which is incorporated herein by reference. Background Art
[0003] With the technological development and growing demand for mobile devices, there is an increasing demand for secondary batteries as an energy source, and among secondary batteries, lithium secondary batteries have been marketed and widely used due to their high energy density, high operating potential, long cycle life and low self-discharge rate.
[0004] In recent years, as people pay more and more attention to environmental issues, many studies have been conducted on electric vehicles (EV) and hybrid electric vehicles (HEV), which are alternatives to vehicles using fossil fuels such as gasoline vehicles and diesel vehicles, which are considered to be one of the main causes of air pollution. Lithium secondary batteries with high energy density, high discharge voltage and stable output have been mainly studied and used as power sources for electric vehicles and hybrid electric vehicles.
[0005] The lithium secondary battery has a structure in which an electrode assembly includes a positive electrode and a negative electrode, each electrode includes an electrode collector and an active material coated on the electrode collector, wherein a porous separator is interposed between the positive electrode and the negative electrode, and a nonaqueous electrolyte including a lithium salt is wetted to the electrode assembly.
[0006] At present, the lithium secondary battery market is controlled by the technology of lithium cobalt oxide LiCoO2 at the positive electrode based on pairing and graphite at the negative electrode. The rated voltage of lithium secondary batteries is about 3.6 V, while the rated voltage of most other types of batteries (Ni-Cd, Ni-MH, etc.) is 1.5 V. The energy density per unit volume and the energy density per unit mass are respectively about 300 to 500Wh / l and 160 to 200 Wh / kg. This value is the highest value among all batteries currently on the market. In addition, this type of battery has low self-discharge and long life (500 or 1000 cycles). Despite the surprising performance achievements, the performance difference between all lithium ion batteries is not great at present, and it is foreseen that improvements will only be carried out in a very limited range.
[0007] Therefore, lithium-sulfur (Li-S) batteries are emerging as an alternative to known lithium-ion batteries.
[0008] In the same way as lithium-ion secondary batteries, lithium-sulfur batteries work by moving lithium ions in an electrolyte between the positive electrode and the negative electrode. However, in contrast to lithium-ion secondary batteries, which aim to store energy by reactions in which lithium ions are embedded in the molecules of the electrode active material, lithium-sulfur batteries work based on oxidation and reduction reactions between sulfur and lithium ions because they use only sulfur, causing changes in the electrode structure. Therefore, compared to lithium-ion secondary batteries, lithium-sulfur batteries can theoretically have a higher capacity at the same volume without restrictions on the electrode structure. Due to this feature, in a lithium-sulfur battery comprising a sulfur positive electrode and a lithium metal negative electrode, when it is assumed that elemental sulfur (S8) with a ring structure is completely reduced to lithium sulfide (Li2S), the theoretical capacity is 1,675 mAh / g and the theoretical energy density is 2,600 Wh / kg, which are 3 to 6 times higher than other existing battery systems (Ni / MH battery: 450 Wh / kg, Li / FeS: 480 Wh / kg, Li / MnO2: 1,000 Wh / kg, Na / S: 800 Wh / kg).
[0009] On the other hand, existing transition metal oxide-based lithium-ion secondary batteries can be considered as batteries containing materials that are sources of heavy metal pollution, because they contain oxides of nickel (Ni), cobalt (Co), and manganese (Mn) in the positive electrode with a density higher than that of heavy metals (metals above 5 g / mL). However, lithium-sulfur batteries do not contain materials that cause pollution and contain non-toxic materials, so they are considered environmentally friendly in this respect. In addition, sulfur, a positive electrode material, is abundant and inexpensive on Earth.
[0010] On the other hand, in lithium-sulfur batteries, sulfur undergoes a reduction reaction and lithium metal undergoes an oxidation reaction during discharge, and in this case, sulfur forms linear-structured lithium polysulfide (LiPS) from a ring-structured S8, and the lithium-sulfur battery shows a step-type discharge voltage until the lithium polysulfide is completely reduced to Li2S. However, while the lithium-sulfur battery is charged and discharged, the charge and discharge efficiency decreases and the battery life is shortened. As described above, the shortened life of the lithium-sulfur battery is caused by many different factors such as side reactions of the electrolyte, instability of lithium metal, and accumulation of positive electrode byproducts (e.g., lithium polysulfide dissolution from the positive electrode).
[0011] That is, in a lithium-sulfur battery using a sulfur compound as a positive electrode active material and an alkali metal such as lithium as a negative electrode active material, lithium polysulfide is dissolved during charging and discharging, and the lithium polysulfide leaked from the positive electrode migrates to the negative electrode, which reduces the capacity of the lithium-sulfur battery and shortens the life of the lithium-sulfur battery. That is, because the lithium polysulfide leaked from the positive electrode has a high solubility in the electrolyte, the lithium polysulfide may inadvertently migrate to the negative electrode through the electrolyte through the separator, causing irreversible loss of the positive electrode active material, thereby causing capacity decay, and sulfur particles accumulate on the surface of the lithium metal due to side reactions, resulting in a shortened battery life.
[0012] In order to solve the problem of shortened life caused by lithium polysulfide, research has been conducted in the art to add reaction mitigation materials to the negative electrode to prevent side reactions from occurring on the surface of lithium metal, but no significant results have been achieved. Summary of the invention
[0013] Technical issues
[0014] One embodiment of the present invention is to provide a block copolymer capable of capturing lithium polysulfide leaked from a positive electrode to improve the life of a lithium-sulfur battery.
[0015] Another embodiment of the present invention is directed to providing a cross-linked block copolymer produced by polymerization of a block copolymer.
[0016] Another embodiment of the present invention is to provide a sulfur-carbon composite material capable of capturing lithium polysulfide leaked from a positive electrode to improve the life of a lithium-sulfur battery.
[0017] Another embodiment of the present invention is directed to a method for manufacturing a sulfur-carbon composite material.
[0018] Technical Solution
[0019] In order to solve the above-mentioned problems of the present invention, a block copolymer, a cross-linked block copolymer including the block copolymer, a sulfur-carbon composite material, and a method of manufacturing the sulfur-carbon composite material according to the following embodiments are provided.
[0020] According to a first embodiment, there is provided a block copolymer comprising:
[0021] a first block comprising a first repeating unit having a pyrene group at a terminal end; and
[0022] The second block comprises a second repeating unit having a cationic functional group.
[0023] According to the second embodiment, in the first embodiment, a molar ratio of the first block to the second block may be 1:99 to 99:1.
[0024] According to the third embodiment, in the first or second embodiment, the first repeating unit may be a product of a reaction between a carboxylic acid compound having a pyrene group at the terminal and an alcohol compound having a (meth)acrylate group.
[0025] According to a fourth embodiment, in any one of the first to third embodiments, the first repeating unit may be represented by the following Chemical Formula 1:
[0026] [Chemical formula 1]
[0027]
[0028] Wherein in Chemical Formula 1,
[0029] R 1 is a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms,
[0030] R 2 is hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and
[0031] n is 0 to 1,000,000.
[0032] According to a fifth embodiment, in any one of the first to fourth embodiments, the second repeating unit may comprise the following Chemical Formula 2:
[0033] [Chemical formula 2]
[0034]
[0035] Wherein in Chemical Formula 2,
[0036] R 3 is hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms,
[0037] R 4 is a linking group or an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms,
[0038] R 5 For-NR 6 R 7 , and R 6 and R 7 Each is independently hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0039] According to the sixth embodiment, in any one of the first to fifth embodiments, the first repeating unit may be represented by the following Chemical Formula 3, and the second repeating unit may be represented by the following Chemical Formula 4:
[0040] [Chemical formula 3]
[0041]
[0042] Wherein in Chemical Formula 3, n is 1 to 1,000,000,
[0043] [Chemical formula 4]
[0044]
[0045] In Chemical Formula 4, m is 1 to 1,000,000.
[0046] According to a seventh embodiment, there is provided a cross-linked block copolymer, the cross-linked block copolymer comprising:
[0047] a first block copolymer and a second block copolymer having the same structure as the first block copolymer and cross-linked with the first block copolymer,
[0048] wherein the first block copolymer is a block copolymer according to any one of the first to sixth embodiments.
[0049] According to the eighth embodiment, in the seventh embodiment, the cationic functional group included in the first block copolymer and the cationic functional group included in the second block copolymer may be cross-linked with each other by a cross-linking agent.
[0050] According to a ninth embodiment, there is provided a sulfur-carbon composite material, the sulfur-carbon composite material comprising:
[0051] Porous carbon materials;
[0052] a coating on at least one surface of the porous carbon material, the coating comprising the cross-linked block copolymer according to any one of the seventh and eighth embodiments; and
[0053] A sulfur compound present in at least a portion of the surface of the porous carbon material or the inside of the pores of the porous carbon material or the surface of the coating layer.
[0054] According to the tenth embodiment, in the ninth embodiment, a weight ratio of the porous carbon material to the cross-linked block copolymer may be 95:5 to 85:15.
[0055] According to the eleventh embodiment, in the ninth or tenth embodiment, a weight ratio of the porous carbon material coated with the cross-linked block copolymer to the sulfur compound may be 3:7 to 4:6.
[0056] According to a twelfth embodiment, a lithium-sulfur battery is provided, wherein the lithium-sulfur battery comprises:
[0057] Positive electrode, negative electrode and separator between the positive electrode and the negative electrode,
[0058] wherein the positive electrode comprises the sulfur-carbon composite material according to any one of the ninth to eleventh embodiments.
[0059] According to a thirteenth embodiment, there is provided a method for manufacturing a sulfur-carbon composite material, the method comprising the following steps:
[0060] introducing the block copolymer according to any one of the first to sixth embodiments into a dispersion of a porous carbon material to coat the block copolymer on at least one surface of the porous carbon material;
[0061] cross-linking the block copolymer coated on the porous carbon material to form a cross-linked block copolymer; and
[0062] The sulfur compound is loaded into the porous carbon material coated with the cross-linked block copolymer.
[0063] According to the fourteenth embodiment, in the thirteenth embodiment, the cross-linked block copolymer may be formed by adding a cross-linking agent to the porous carbon material coated with the block copolymer and performing a heat treatment.
[0064] According to a fifteenth embodiment, in the fourteenth embodiment, the cross-linking agent may comprise a dihaloalkane compound.
[0065] Beneficial Effects
[0066] The sulfur-carbon composite material of the present invention comprises a cross-linked block copolymer, and the cross-linked block copolymer is made of a block copolymer, wherein the block copolymer comprises: a first block, wherein the first block comprises a first repeating unit having a pyrene group at the end; and a second block, wherein the second block comprises a second repeating unit having a cationic functional group.
[0067] Because the cross-linked block copolymer is coated on the sulfur-carbon composite material, the lithium polysulfide leaked from the positive electrode of the lithium-sulfur battery can be prevented from migrating to the negative electrode. Therefore, the sulfur particles can be prevented from accumulating on the lithium metal surface of the negative electrode, thereby maintaining the charge and discharge capacity of the lithium-sulfur battery and improving the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] The accompanying drawings show exemplary embodiments of the present invention and, together with the following detailed description, are used to provide a further understanding of the technical aspects of the present invention, and thus the present invention should not be construed as being limited to the accompanying drawings.
[0069] Figures 1 to 6The synthesis mechanism and synthesis structure of the monomer and block copolymer prepared in Example 1 are shown.
[0070] Figures 7 to 10 This is a graph showing the evaluation of battery discharge capacity by charge and discharge at 25°C. DETAILED DESCRIPTION
[0071] Hereinafter, the present invention will be described in more detail.
[0072] It should be understood that the terms or words used in the specification and the appended claims should not be interpreted as limited to the general and dictionary meanings, but should be interpreted according to the meanings and concepts corresponding to the technical aspects of the present invention, based on the principle that the inventor appropriately defines the terms for the best interpretation.
[0073] Unless the context clearly indicates otherwise, when used in this specification, the terms “comprise” or “include” specify the presence of stated elements, but do not exclude the presence or addition of one or more other elements.
[0074] The terms "about" and "approximately" herein are used in the sense of the value or approximate thereto when given the manufacturing and material tolerances inherent in the circumstances, and are used to prevent unscrupulous infringers from improperly taking advantage of the exact or absolute values set forth in the present invention to aid in the understanding of the present invention.
[0075] The present invention relates to a block copolymer, a cross-linked block copolymer comprising the block copolymer, a sulfur-carbon composite material, a method for manufacturing the sulfur-carbon composite material, an electrochemical cell comprising the same, and a method for manufacturing the same. In the present invention, the electrochemical cell may include any type of battery in which an electrochemical reaction occurs. Specific examples of the electrochemical cell include any type of primary battery, secondary battery, fuel cell, solar cell, and capacitor such as a supercapacitor, etc. In particular, the electrochemical cell may be a secondary battery, and the secondary battery may be a lithium ion secondary battery. The lithium ion secondary battery may include, for example, a lithium metal battery, a lithium sulfur battery, an all-solid-state battery, a lithium polymer battery, etc., wherein a lithium sulfur battery is preferred.
[0076] Among secondary batteries, lithium-sulfur batteries have high discharge capacity and theoretical energy density, and because sulfur used as a positive electrode active material is abundant and inexpensive on Earth, the battery manufacturing cost required for lithium-sulfur batteries is low and environmentally friendly, so they are attracting attention as next-generation secondary batteries.
[0077] In the present invention, the positive electrode active material includes a carbon-sulfur composite material, and the carbon-sulfur composite material includes a porous carbon material. In lithium-sulfur batteries, since the positive electrode active material sulfur is not conductive, a carbon-sulfur composite material in which a conductive material such as a carbon material is combined with sulfur is generally used to improve conductivity.
[0078] According to one aspect of the present invention, there is provided a block copolymer, the block copolymer comprising:
[0079] a first block comprising a first repeating unit having a pyrene group at a terminal end; and
[0080] The second block comprises a second repeating unit having a cationic functional group.
[0081] According to one embodiment of the present invention, the molar ratio of the first block to the second block can be appropriately selected as needed. For example, the molar ratio can be 1:99 to 99:1. In addition, the weight average molecular weight of the block copolymer can be appropriately selected as needed. For example, the weight average molecular weight of the block copolymer can be 10 to 5,000,000.
[0082] According to one embodiment of the present invention, the first block may be derived from the first repeating unit. In addition, the second block may be derived from the second repeating unit.
[0083] For example, the first block may be prepared via chain transfer polymerization of the first repeating unit, and the second block may be prepared via chain transfer polymerization of the second repeating unit. In this case, the degree of polymerization of each of the first block and the second block may be 10 to 1,000,000.
[0084] According to one embodiment of the present invention, the first repeating unit may be a product of a reaction between a carboxylic acid compound having a pyrene group at a terminal and an alcohol compound having a (meth)acrylate group.
[0085] For example, the carboxylic acid compound having a pyrene group at the terminal may be represented by Chemical Formula 1 as follows.
[0086] [Chemical formula 1]
[0087]
[0088] In the above chemical formula 1, R 1 It may be a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms.
[0089] For example, the carboxylic acid compound may be 1-pyrenebutyric acid. That is, in the above chemical formula 1, R 1 It may be a propyl group having 3 carbon atoms.
[0090] For example, the alcohol compound having a (meth)acrylate group may be represented by Chemical Formula 2 below.
[0091] [Chemical formula 2]
[0092]
[0093] In the above chemical formula 2, R 2 It may be hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and n may be 0 to 1,000,000.
[0094] For example, the alcohol compound may be poly(ethylene glycol) methyl ether methacrylate. That is, in the above Chemical Formula 2, R 2 It may be hydrogen.
[0095] For example, the first repeating unit may be represented by Chemical Formula 3 as follows.
[0096] [Chemical formula 3]
[0097]
[0098] According to one embodiment of the present invention, the cationic functional group may include a functional group having a nitrogen atom. The cationic functional group may adsorb polysulfide.
[0099] According to one embodiment of the present invention, the first repeating unit may include Chemical Formula 4 as follows.
[0100] [Chemical formula 4]
[0101]
[0102] In the above Chemical Formula 4, n is 1 to 1,000,000.
[0103] According to one embodiment of the present invention, the second repeating unit may include Chemical Formula 5 below.
[0104] [Chemical formula 5]
[0105]
[0106] In the above chemical formula 5,
[0107] R 3 may be hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms,
[0108] R 4 may be a linking group or an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms,
[0109] R 5 Can be -NR 6 R 7 , and R6 and R 7 Each may independently be hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0110] For example, the second repeating unit may be represented by Chemical Formula 6 as follows.
[0111] [Chemical formula 6]
[0112]
[0113] In the above Chemical Formula 6, m may be 0 to 1,000,000.
[0114] According to one embodiment of the present invention, the block copolymer can be formed by polymerization of the first block and the second block via chain transfer polymerization. For example, after dissolving the first block, the second block, a chain transfer agent (CTA) and a thermal initiator (e.g., azobisisobutyronitrile (AIBN)) in diblock, After adding the alkane solvent and removing oxygen from the solution, polymerization can be carried out at a high temperature (e.g., 80° C.). For example, the chain transfer agent can be 4-cyano-4-(((tridecylthio)thiocarbonyl)thio)pentanoic acid. Subsequently, precipitation in diethyl ether and purification can be carried out to prepare a block copolymer.
[0115] According to one embodiment of the present invention, a block copolymer including a first block and a second block may be represented by Chemical Formula 7 as follows.
[0116] [Chemical formula 7]
[0117]
[0118] In the above Chemical Formula 7, m, n, and k may each be 0 to 1,000,000.
[0119] According to another aspect of the present invention, there is provided a cross-linked block copolymer, the cross-linked block copolymer comprising:
[0120] a first block copolymer and a second block copolymer having the same structure as the first block copolymer and cross-linked with the first block copolymer,
[0121] The first block copolymer is any one of the above block copolymers.
[0122] According to one embodiment of the present invention, the cross-linked block copolymer can be formed by cross-linking the first block copolymer and the second block copolymer, specifically, the cationic functional groups of the first block copolymer and the cationic functional groups of the second block copolymer are cross-linked by a cross-linking agent. The cross-linking agent is not limited to a specific type, but can include, for example, a dihalogenated alkane compound (e.g., diiodobutane).
[0123] According to another aspect of the present invention, there may be a sulfur-carbon composite material, the sulfur-carbon composite material comprising:
[0124] Porous carbon materials;
[0125] a coating on at least one surface of the porous carbon material, the coating comprising the cross-linked block copolymer described above; and
[0126] A sulfur compound present in at least a portion of the surface of the porous carbon material or the inside of the pores or the surface of the coating layer.
[0127] The porous carbon material includes a plate-like carbon material. The specific surface area of the porous carbon material is 1,000 m 2 / g or more, and the pore volume of the porous carbon material is 4 cm 3 / g or above.
[0128] Porous carbon materials are characterized by high specific surface area to increase the active sites for sulfur to participate in oxidation / reduction reactions. In addition, porous carbon materials are characterized by high pore volume to ensure high sulfur loading and sufficient ion diffusion paths.
[0129] The sulfur-carbon composite material comprises a porous carbon material as a carrier for carrying sulfur-containing compounds. Specifically, the sulfur-carbon composite material comprises a plate-like porous carbon material as the porous carbon material. The plate-like porous carbon material may include, for example, graphene, graphene oxide, reduced graphene oxide (rGO) or a mixture thereof.
[0130] In one embodiment of the present invention, the plate-like porous carbon material may include only reduced graphene oxide.
[0131] Porous carbon materials have a 1,000 m 2 Specifically, the upper limit of the Brunauer-Emmett-Teller (BET) specific surface area of the porous carbon material is not limited to a specific range, and may be, for example, 1,000 m 2 / g or more and 1,500 m 2 / g or less, 1,300 m 2 / g or less, 1,200 m 2 / g or less, 1,100 m 2 / g or less, 1,050 m2 The sulfur-carbon composite material according to the present invention contains a plurality of micropores on its outer surface and / or inside and has a very high specific surface area.
[0132] The BET specific surface area can be measured by the BET method and indicates a value measured by a known method for measuring the BET specific surface area. For example, the BET specific surface area can be a value calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-max of BEL Japan.
[0133] The porous carbon material has a 4 cm 3 Specifically, the upper limit of the pore volume of the porous carbon material is not limited to a specific range, and may be, for example, 4 cm 3 / g or more and 15 cm 3 / g or less, 6 cm 3 / g or more and 10 cm 3 / g or less, 6cm 3 / g or more and 8 cm 3 / g or less or 6.5 cm 3 / g or more and 7.5 cm 3 For example, the pore volume may be a measured value calculated by N2 isotherm analysis obtained based on liquid nitrogen adsorption.
[0134] As described above, the porous carbon material in the sulfur-carbon composite material according to one aspect of the present invention includes a plurality of micropores to support the sulfur-containing compound.
[0135] In one embodiment of the present invention, the porous carbon material comprises a plurality of micropores on its outer surface and inside, and in this case, the micropores comprise mesopores having a diameter of 1 nm or more and less than 50 nm and macropores having a diameter of 50 nm or more and 200 nm or less. In one embodiment of the present invention, the porous carbon material preferably has uniformly distributed mesopores and macropores.
[0136] The diameter of the micropores can be measured by methods known in the art for measuring the pore size of porous materials, and the measuring method is not limited to a specific type. For example, the average diameter of the micropores can be measured by scanning electron microscopy (SEM), field emission electron microscopy or laser diffraction. Measurement using laser diffraction can use, for example, a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac MT 3000).
[0137] In another embodiment of the present invention, the average pore diameter (D50) of the porous carbon material may be, for example, 20 nm to 25 nm, but is not limited thereto. The average diameter (D50) refers to the particle diameter at 50% in the cumulative particle size distribution.
[0138] In the present invention, the sulfur compound is contained in at least a part of the inside and the outer surface of the pores of the porous carbon material having the above-mentioned characteristics.
[0139] The sulfur compound may include, but is not limited to, any type of sulfur compound that can be used as a positive electrode active material in a lithium-sulfur secondary battery. For example, the sulfur compound may include inorganic sulfur (S8), lithium polysulfide (Li2S n , 1≤n≤8), carbon-sulfur polymer (C2S x ) m , 2.5≤x≤50, 2≤m) or a mixture thereof, but not limited thereto.
[0140] The sulfur compound may be included in the sulfur-carbon composite material by physical adsorption on the porous carbon material or by a chemical bond such as a covalent bond, a van-deer-Waals bond, etc. between sulfur and carbon in the porous carbon material.
[0141] In one embodiment of the present invention, the porous carbon material and the sulfur compound may be included in the sulfur-carbon composite material in a weight ratio of, for example, 1:9 to 9:1, specifically 1:9 to 5:5, 1:9 to 4:6, 1:9 to 3:7, or 1:9 to 1.5:8.5. When the weight ratio of the porous carbon material to the sulfur compound in the sulfur-carbon composite material is within the above range, the kinetic activity of the sulfur-carbon composite material may be increased and the conductivity may be improved by the porous carbon material because the content of the sulfur compound is large, but the present invention is not limited thereto.
[0142] In another embodiment of the present invention, the amount of the sulfur compound in the sulfur-carbon composite material can be, for example, 10% by weight or more, specifically 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, or 85% by weight or more, based on the total weight of the sulfur-carbon composite material. In addition, based on the total weight of the sulfur-carbon composite material, the amount of the sulfur compound in the sulfur-carbon composite material can be 50% by weight to 90% by weight within the above range, specifically 60% by weight to 90% by weight, 70% by weight to 90% by weight, or 85% by weight to 90% by weight. When the amount of the sulfur compound in the sulfur-carbon composite material is within the above range, because the content of the sulfur compound is large, the kinetic activity of the sulfur-carbon composite material can be increased and the conductivity can be improved by the porous carbon material, but the present invention is not limited thereto.
[0143] In one embodiment of the present invention, the average particle size (D50) of the sulfur-carbon composite material can be, for example, 0.5 μm to 200 μm, 1 μm to 150 μm, or 10 μm to 150 μm. The particle size of the sulfur-carbon composite material can be measured by SEM, field emission electron microscopy or laser diffraction. Measurement using laser diffraction can use, for example, a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac MT 3000). The average particle size (D50) refers to the particle size at 50% in the cumulative particle size distribution.
[0144] In one embodiment of the present invention, the Raman peak intensity ratio (I G / I D The ratio may be less than 1. For example, when I G / I D When the ratio is greater than 1, since the surface crystallinity of the sulfur-carbon composite material is high, the efficiency of the combination with the sulfur-containing compound or the conversion reaction of lithium polysulfide may be low, but is not limited thereto.
[0145] The Raman peak intensity ratio can be obtained by the I obtained from the spectrum of the carbon composite material obtained by Raman spectroscopy. G and I D In the obtained spectrum, I G The peak representing the crystalline part (G peak, 1,573 / cm), and I D Indicates the peak of the amorphous part (D peak, 1,309 / cm). Therefore, in this case, I G / I D The smaller the ratio, the lower the crystallinity.
[0146] In one embodiment of the present invention, the sulfur-carbon composite material may be formed by mixing a porous carbon material with a sulfur compound and performing a heat treatment, but the manufacturing method of the present invention is not limited thereto.
[0147] Because the sulfur-carbon composite material of the present invention as described above includes a plate-like carbon material having a high specific surface area and a high pore volume, the sulfur loading amount can be enhanced and multiple active sites for sulfur oxidation / reduction reactions can be provided, thereby improving battery efficiency and energy density when used for the positive electrode of a lithium-sulfur battery, but the mechanism of the present invention is not limited thereto.
[0148] In one embodiment of the present invention, the coating layer may include the cross-linked block copolymer. For example, the weight ratio of the porous carbon material to the cross-linked block copolymer may be 95:5 to 85:15. In addition, the weight ratio of the porous carbon material coated with the cross-linked block copolymer to the sulfur compound may be 3:7 to 4:6.
[0149] According to another aspect of the present invention, there is provided a method for manufacturing a sulfur-carbon composite material, the method comprising the following steps:
[0150] introducing the block copolymer into a dispersion of a porous carbon material to coat the block copolymer on at least one surface of the porous carbon material;
[0151] cross-linking the block copolymer coated on the porous carbon material to form a cross-linked block copolymer; and
[0152] Sulfur is loaded into porous carbon materials coated with cross-linked block copolymers.
[0153] In one embodiment of the present invention, the porous carbon material (e.g., Ketjen black (KB)) and the chloride (e.g., FeCl3) can be dispersed in a solvent. For example, the solvent is not limited to a specific type and can include any type of solvent that can dissolve or disperse the compound. The solvent can be, for example: a chlorine-containing solvent such as chloroform, dichloromethane, 1,2-dichloroethane, 1,1,2-trichloroethane, chlorobenzene, o-dichlorobenzene; an ether solvent such as tetrahydrofuran, dichloroethane; Alkanes; aromatic hydrocarbon solvents such as toluene, xylene, trimethylolene, mesitylene; aliphatic hydrocarbon solvents such as cyclohexane, methylcyclohexane, n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone; ester solvents such as ethyl acetate, butyl acetate, ethyl cellosolve acetate; polyols such as ethylene glycol, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, dimethoxyethane, propylene glycol, diethoxymethane, triethylene glycol monoethyl ether, glycerol, 1,2-hexanedialdehyde and its derivatives; alcohol solvents such as methanol, ethanol, propanol, isopropanol, cyclohexanol; sulfoxide solvents such as dimethyl sulfoxide; amide solvents such as N-methyl-2-pyrrolidone, N,N-dimethylformamide; benzoate solvents such as butyl benzoate, methyl 2-methoxybenzoate; tetralin; 3-phenoxytoluene.
[0154] Subsequently, after the block copolymer is introduced into the dispersion of the porous carbon material, coating may be performed at room temperature for 24 hours. For example, the weight ratio of the porous carbon material to the block copolymer may be 95:5 to 85:15.
[0155] Subsequently, a crosslinking agent (eg, a dihalogenated alkane compound such as diiodobutane) is added to the dispersion of the porous carbon material coated with the block copolymer, and heat-treated at about 45° C. for 24 hours to crosslink the block copolymer in the porous carbon material.
[0156] Subsequently, the sulfur compound can be loaded into the porous carbon material coated with the cross-linked block copolymer and heat-treated to prepare a sulfur-carbon composite material. For example, the weight ratio of the porous carbon material coated with the cross-linked block copolymer to the sulfur compound can be 3:7 to 4:6.
[0157] Because the cross-linked block copolymer is coated on the porous carbon material, the lithium polysulfide leaked from the positive electrode of the lithium-sulfur battery can be prevented from migrating to the negative electrode. Therefore, sulfur particles can be prevented from accumulating on the lithium metal surface of the negative electrode, thereby maintaining the charge and discharge capacity of the lithium-sulfur battery and improving the battery life.
[0158] Hereinafter, embodiments will be described in detail to help better understand the present invention. However, examples according to the present invention can be changed in many other forms, and the scope of the present invention should not be interpreted as being limited to the following examples. Embodiments of the present invention are provided to fully illustrate the present invention to those of ordinary skill in the art.
[0159] Example 1
[0160] Preparation of block copolymers
[0161] 1) Preparation of the first monomer: 1-pyrenebutyric acid (PBA) and poly (ethylene glycol) methyl ether methacrylate (PEGMA) were reacted in a toluene solvent at 110° C. under a p-toluenesulfonic acid (pTsOH) catalyst to synthesize PEGMA-PBA (hereinafter referred to as PP). The synthesized PP was purified by extraction with H2O / MC (dichloromethane) three times.
[0162] The detailed synthesis mechanism is shown in Figure 1 and through 1 H NMR was used to observe the structure of the synthesized monomer and the results are shown in Figure 2 middle.
[0163] 2) Preparation of the second monomer: Dissolve dimethylaminoethyl acrylate (DMAEMA), chain transfer agent (CTA, 4-cyano-4-(((tridecylthio)carbonylthio)thio)pentanoic acid) and AIBN in distilled water. The reaction mixture was stirred for 3 hours in 1% ethanol and subjected to freeze-pump-thaw cycles three times to remove oxygen from the solution. The oxygen-free solution was polymerized at 80°C. The crude polymer product was purified by precipitation in hexane three times to obtain poly(dimethylamino)ethyl methacrylate (PDMAEMA).
[0164] The detailed synthesis mechanism is shown in Figure 3 and through 1 The structure of the synthesized monomer was observed by H NMR and GPC analysis, and the results are shown in Figure 4 middle.
[0165] 3) Preparation of block copolymer: The first monomer and the second monomer prepared as described above (first monomer: second monomer = 1:1, based on molar ratio), CTA (4-cyano-4-(((tridecylthio)carbonylthio)thio)pentanoic acid) and AIBN were dissolved in distilled water. The PDbPP was prepared by precipitating the PDbPP in diethyl ether for 3 times.
[0166] The detailed synthesis mechanism is shown in Figure 5 In this paper, the structure of the synthesized PDbPP is described by 1 The results were observed by H NMR and GPC analysis. Figure 6 middle.
[0167] Preparation of sulfur-carbon composite materials
[0168] 1) Ketjen black (KB) and FeCl3 were dispersed in chloroform solvent by ultrasonication for 3 hours.
[0169] 2) PDbPP (10 wt % compared to KB) was dissolved in chloroform, added dropwise to the KB dispersion, and stirred at room temperature for 24 hours to form a coating.
[0170] 3) Diiodobutane was added dropwise to the dispersion of KB coated with PDbPP, and a reaction was caused at 45° C. for 24 hours to crosslink the coated PDbPP to obtain CPDbPP10-KB.
[0171] 4) CPDbPP10-KB and sulfur were crushed and mixed (CPDbPP10-KB: S = 7: 3, wt / wt), and heat-treated at 155 °C for 30 min to load sulfur to obtain CPDbPP10-KB-S.
[0172] positive electrode
[0173] A sulfur compound was loaded into Ketjen black coated with a cross-linked block copolymer as a positive electrode active material to prepare a sulfur-carbon composite material (CPDbPP10-KB-S).
[0174] The sulfur-carbon composite material, PAA binder (poly(acrylic acid)) and carbon conductive material were mixed in a weight ratio of 85:10:5, 0.5 wt% of PVA dispersant was added to prepare a positive electrode slurry with a solid concentration of 18 wt%, and the positive electrode slurry was uniformly coated on an aluminum foil to a thickness of 400 μm and dried at 50° C. to prepare a positive electrode. The weight ratio of the cross-linked block copolymer to the positive electrode was 8.5 wt%.
[0175] Separator, anode and electrolyte
[0176] For the separator, a polyethylene porous film (Celgard separator) was used, and for the negative electrode, lithium metal was used. 1.0 M LiNO3 was added to a mixed solvent of 1,3-dioxolane (DOL) and 1,2-dimethyl ether in a volume ratio (volume / volume) of 50:50 to prepare an electrolyte for a lithium-sulfur secondary battery.
[0177] Comparative Example 1
[0178] positive electrode
[0179] A positive electrode was prepared by the same method as in Example 1, except that a sulfur-carbon composite material in which Ketjen black and a sulfur compound were mixed at a weight ratio of 3:7 was used as a positive electrode active material.
[0180] Separator, anode and electrolyte
[0181] The separator, negative electrode and electrolyte were prepared by the same method as in Example 1.
[0182] Comparative Example 2
[0183] positive electrode
[0184] (1) A sulfur compound is loaded into Ketjen black as a positive electrode active material, (2) a block copolymer is coated on the Ketjen black loaded with the sulfur compound, and (3) the block copolymer is cross-linked to prepare a sulfur-carbon composite material comprising a cross-linked block copolymer. The sulfur-carbon composite material, the PAA binder, and the carbon conductive material are mixed in a weight ratio of 85:10:5, 0.5 wt % of a PVA dispersant is added to prepare a positive electrode slurry having a solid concentration of 18 wt %, and the positive electrode slurry is uniformly coated on an aluminum foil to a thickness of 400 μm and dried at 50° C. to prepare a positive electrode. The weight ratio of the cross-linked block copolymer to the positive electrode is 3 wt %.
[0185] Separator, anode and electrolyte
[0186] The separator, negative electrode and electrolyte were prepared by the same method as in Example 1.
[0187] Comparative Example 3
[0188] positive electrode
[0189] A positive electrode was prepared by the same method as Comparative Example 2, except that the Ketjen black coated with the cross-linked block copolymer was mixed with the sulfur compound at a weight ratio of 1:9 (CPDbPP10-KB:S=1:9, weight / weight).
[0190] Separator, anode and electrolyte
[0191] The separator, negative electrode and electrolyte were prepared by the same method as in Example 1.
[0192] Comparative Example 4
[0193] positive electrode
[0194] A positive electrode was prepared by the same method as in Comparative Example 2, except that the weight ratio of the cross-linked block copolymer to the positive electrode was 1 wt %.
[0195] Separator, anode and electrolyte
[0196] The separator, negative electrode and electrolyte were prepared by the same method as in Example 1.
[0197] Comparative Example 5
[0198] positive electrode
[0199] A positive electrode was prepared by the same method as in Comparative Example 2, except that the weight ratio of the cross-linked block copolymer to the positive electrode was 5 wt %.
[0200] Separator, anode and electrolyte
[0201] The separator, negative electrode and electrolyte were prepared by the same method as in Example 1.
[0202] Figure 7 This is a graph of the discharge capacity evaluated by charge and discharge at 25° C. under the following conditions.
[0203] Tester: WBSC3000 Battery Cycler (WonAtech)
[0204] Current density: 0.2 C rate
[0205] refer to Figure 7 , when measured, the lithium-sulfur battery according to Example 1 had a higher discharge capacity in 1 cycle to 100 cycles than the lithium-sulfur battery according to Comparative Example 1.
[0206] Figure 8 This is a graph of the discharge capacity evaluated by charge and discharge at 25° C. under the following conditions.
[0207] Tester: WBSC3000 Battery Cycler (WonAtech)
[0208] Current density: 1 C rate
[0209] refer to Figure 8 , when measured, the lithium-sulfur battery according to Example 1 had a higher discharge capacity in 40 cycles to 160 cycles than the lithium-sulfur battery according to Comparative Example 1.
[0210] Fig. 9 and 10 This is a graph of the discharge capacity evaluated by charge and discharge at 25° C. under the following conditions.
[0211] Tester: WBSC3000 Battery Cycler (WonAtech)
[0212] Current density: 0.2 C rate
[0213] refer to Fig. 9 and Fig.10 ,from Fig. 9 It can be seen that, when measured, the discharge capacity of the lithium-sulfur battery according to Example 1 was higher than that of the lithium-sulfur batteries according to Comparative Examples 1 and 2 in 1 cycle to 50 cycles.
[0214] In other words, the measurement shows that forming a coating on the porous carbon material and then loading a sulfur compound contributes to improving the coating properties of the coating, thereby achieving a high discharge capacity, compared with not forming a coating or forming a coating after loading sulfur.
[0215] On the other hand, reference Fig.10 It is confirmed that Comparative Example 2 has a higher discharge capacity than Comparative Examples 1, 4 and 5, but Fig. 9 It can be seen that Comparative Example 2 is worse than Example 1 in which the coating layer was first formed and then the sulfur compound was supported.
Claims
1. A block copolymer, comprising: a first block comprising a first repeating unit having a pyrene group at a terminal end; and The second block comprises a second repeating unit having a cationic functional group. 2 . The block copolymer according to claim 1 , wherein a molar ratio of the first block to the second block is 1:99 to 99:
1. 3 . The block copolymer according to claim 1 , wherein the first repeating unit is a product obtained by a reaction between a carboxylic acid compound having a pyrene group at a terminal and an alcohol compound having a (meth)acrylate group.
4. The block copolymer according to claim 1, wherein the first repeating unit is represented by the following Chemical Formula 1: [Chemical formula 1] Wherein in Chemical Formula 1, R 1 is a linking group, an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms, R 2 is hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and n is 0 to 1,000,000.
5. The block copolymer according to claim 1, wherein the second repeating unit comprises the following Chemical Formula 2: [Chemical formula 2] Wherein in Chemical Formula 2, R 3 is hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms, R 4 is a linking group or an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or an arylene group having 6 to 20 carbon atoms, R 5 For-NR 6 R 7 , and R 6 and R 7 Each is independently hydrogen, an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
6. The block copolymer according to claim 1, wherein the first repeating unit is represented by the following Chemical Formula 3, and The second repeating unit is represented by the following chemical formula 4: [Chemical formula 3] Wherein in Chemical Formula 3, n is 1 to 1,000,000, [Chemical formula 4] In Chemical Formula 4, m is 1 to 1,000,000.
7. A cross-linked block copolymer, comprising: a first block copolymer and a second block copolymer having the same structure as the first block copolymer and cross-linked with the first block copolymer, The first block copolymer is the block copolymer according to any one of claims 1 to 6. 8 . The cross-linked block copolymer according to claim 7 , wherein the cationic functional group included in the first block copolymer and the cationic functional group included in the second block copolymer are cross-linked with each other by a cross-linking agent.
9. A sulfur-carbon composite material, comprising: Porous carbon materials; a coating on at least one surface of the porous carbon material, the coating comprising the cross-linked block copolymer of any one of claims 7 and 8; and A sulfur compound present in at least a portion of the surface of the porous carbon material or the inside of the pores of the porous carbon material or the surface of the coating layer. 10 . The sulfur-carbon composite material according to claim 9 , wherein a weight ratio of the porous carbon material to the cross-linked block copolymer is 95:5 to 85:
15. 11 . The sulfur-carbon composite material according to claim 9 , wherein a weight ratio of the porous carbon material coated with the cross-linked block copolymer to the sulfur compound is 3:7 to 4:
6.
12. A lithium-sulfur battery, comprising: a positive electrode, a negative electrode and a separator between the positive electrode and the negative electrode, The positive electrode comprises the sulfur-carbon composite material according to claim 9.
13. A method for manufacturing a sulfur-carbon composite material, the method comprising the following steps: Introducing the block copolymer according to any one of claims 1 to 6 into a dispersion of a porous carbon material to coat the block copolymer on at least one surface of the porous carbon material; cross-linking the block copolymer coated on the porous carbon material to form a cross-linked block copolymer; and A sulfur compound is loaded into the porous carbon material coated with the cross-linked block copolymer. 14 . The method for producing a sulfur-carbon composite material according to claim 13 , wherein the cross-linked block copolymer is formed by adding a cross-linking agent to the porous carbon material coated with the block copolymer and performing a heat treatment.
15. The method for producing a sulfur-carbon composite material according to claim 14, wherein the cross-linking agent comprises a dihalogenated alkane compound.
Citation Information
Patent Citations
Safety valve for low pressure having improved backflow prevention function
KR1020220110368A